Exploring the justification and efficacy of marketing strategies adapted in Tanzania’s private primary and secondary schools - Kahangwa, George Leonard (Papers in Education and Development, 2024)
This study was conducted in Dar es Salaam, Tanzania, to explore education marketing strategies that private primary and secondary schools use and the extent of their efficacy. The study employed the marketing-mix theory to describe the marketing areas that are of interest to the schools under review. Data were collected through documentary reviews, school observations, and interviews with the heads of selected schools. Thematic and descriptive analyses were used. The study found that inter-school competition emanated from the reintroduction and increase of private schools. The marketing strategies that education managers use under the current education marketing in Tanzania include improving and maintaining the quality of services. Even though the managers were generally satisfied with the output of their strategies, a working strategy for marketing in education must be mindful of what clients consider to be important. It is recommended that school heads should employ strategies that do not compromise education quality.